Tingkat Konsentrasi Siswa Dalam Ekstrakurikuler Panahan - Veny Juniarni Hardi; Deky Adika Hastian (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2022)
This study aims to compare the concentration of students who take extracurricular archery at SMAN Soreang. The method used is descriptive independent sample T Test. The research population is all students of SMAN Soreang. Sampling used a total sampling technique which visited 20 students who took archery extracurricular and 20 students who did not participate in archery extracurricular at random. The instrument used in this research is the Grid Concentration test and processing the data obtained using inferential statistical data analysis. The result of this research is that there are significant differences in concentration levels between students who take and do not take archery extracurriculars. Students who take archery extracurricular tend to have a higher concentration level than students who do not take archery extracurricular.